Results-Sharing System of Punggawa-Sawi in Gillnet Fishermen of Sumpang Binangae Village, Barru District, Barru Regency - Marasin, Fedri Dwiyanto; Tahang, Hamzah; Gosari, Benny Audy Jaya; Adhawati, Sri Suro; Made, Sutinah (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2024)
This study aims to determine the relationship pattern of mustard punggawa to gillnet fishermen and to find out the income and remuneration system of mustard punggawa to gillnet fishermen, Sumpang Binangae Village, Barru District, Barru Regency. This research was carried out from February to March 2021 with two main respondents, namely retainers and mustards for gillnet fishermen in Sumpang Binangae Village, Barru District, Barru Regency. The sampling method in this research is purposive sampling. The data sources used are primary data and secondary data. Data analysis using descriptive qualitative analysis and quantitative descriptive using the formula for production costs, revenues and profits. The pattern of the punggawa-sawi fisherman's working relationship in recruiting mustard greens, Mr. burhanuddin (the punggawa-sawi fisherman group A) prefers to prioritize his family who are looking for work for him. While on the other hand, Mr. dg. Nai' (the punggawa-sawi fisherman group B) chose the mustards who worked for him not only based on kinship but friendship. Then the income of the retainer-sawi fisherman group (A) is IDR 454,530,000 per year and the wage system is the retainer's wage of 65%, while the mustard greens get 35% of the catch. The income of the retainer-sawi fisherman group (B) is Rp. 266.673,333 per year and the wage system is the retainer's wages of 50% while the mustard greens get 50% of the catch.